Essentials of diagnosis and prevention of genetic diseases in the primary health care. - Julia Surí González; María Antonia Ocaña Gil; María del Rosario Liriano Ricabal; Luisa Días Requeiro; Antonio Masót Rangel; Sonia González Sosa (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Programs aimed at preventing genetic diseases reduce their fatal consequences among the population. Therefore, it is important to correctly prepare the medical staff working in the Maternal-Infant Program. Subjects related with these issues are thought since the pre-graduate education, in the second year of Medicine studies and in the postgraduate courses as part of the General Comprehensive Medicine residency within the subject Medical Genetics. The importance of this topic supported the creation of this pamphlet, based on a bibliographical review of the subject related with the implementation of the diagnosis and prevention program for genetic disease within the practice of genetic advising. The objective of this pamphlet is to provide the basic theoretical elements to facilitate the implementation of health actions in the community, which can be further review using the conventional bibliography.